Comparing air quality among Italy, Germany and Poland using BC indexes - Olha Bodnar; Michela Cameletti; Alessandro Fassò; Wolfgang Schmid (European University Viadrina, Department of Business Administration and Economics, 2008)
In this paper we discuss air quality assessment in three Italian, German and Polish regions using the index methodology proposed in Bruno and Cocchi (2002, 2007). This analysis focuses first of all on the quality of the air in each of the countries being taken into consideration, and then adopts a more general approach in order to compare pollution severity and toxicity. This is interesting in a global European perspective where all countries are commonly involved in assessing air quality and taking proper measures for improving it. In this context, air quality indexes are a powerful data-driven tool which are easily calculated and summarize a complex phenomenon, such as air pollution, in indicators which are immediately understandable. In particular, the main objective of this work is to evaluate the index performances in distinguishing different air pollution patterns. This kind of analysis can be particularly useful, for example, in the perspective of constructing an indicator of air pollution.
Keywords: 330